√41-12√5 -41+12√5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
\(\sqrt{41-12\sqrt{5}}-\sqrt{41+12\sqrt{5}}=\sqrt{6^2+5-2.6\sqrt{5}}-\sqrt{6^2+5+2.6\sqrt{5}}\)
\(=\sqrt{(6-\sqrt{5})^2}-\sqrt{(6+\sqrt{5})^2}=|6-\sqrt{5}|-|6+\sqrt{5}|\)
\(=(6-\sqrt{5})-(6+\sqrt{5})=-2\sqrt{5}\)
\(\left(\dfrac{11}{14}+\dfrac{13}{24}\right)+\left(\dfrac{-5}{41}-\dfrac{36}{41}\right)+0,5\)
= 1 + (-1) + 0,5
= 0 + 0,5
= 0,5
= (-5/12 + 17/12) + ( 4/37 - 41/37)
= 12/12 + (-37/37)
=1 + (-1)
=0
\(a,x-36:18=12-15\\ \Rightarrow x-2=-3\\ \Rightarrow x=-1\\ b,92-\left(17+x\right)=72\\ \Rightarrow17+x=20\\ \Rightarrow x=3\\ c,720:\left[41-\left(2x+5\right)\right]=40\\ \Rightarrow41-\left(2x+5\right)=18\\ \Rightarrow2x+5=23\\ \Rightarrow2x=18\\ \Rightarrow x=9\\ d,\left(x+2\right)^3-23=41\\ \Rightarrow\left(x+2\right)^3=64\\ \Rightarrow\left(x+2\right)^3=4^3\\ \Rightarrow x+2=4\\ \Rightarrow x=2\)
\(\sqrt{41-12\sqrt{5}}-\sqrt{41+12\sqrt{5}}\)
\(=\sqrt{36-12\sqrt{5}+5}-\sqrt{36+12\sqrt{5}+5}\)
\(=\sqrt{6^2-2\cdot6\cdot\sqrt{5}+\left(\sqrt{5}\right)^2}-\sqrt{6^2+2\cdot6\cdot\sqrt{5}+\left(\sqrt{5}\right)^2}\)
\(=\sqrt{\left(6-\sqrt{5}\right)^2}-\sqrt{\left(6+\sqrt{5}\right)^2}\)
\(=\left|6-\sqrt{5}\right|-\left|6+\sqrt{5}\right|\)
\(=6-\sqrt{5}-6-\sqrt{5}\)
\(=-2\sqrt{5}\)